1994
DOI: 10.1007/bf00347531
|View full text |Cite
|
Sign up to set email alerts
|

Sun-compass migration by Aurelia aurita (Scyphozoa): population retention and reproduction in Saanich Inlet, British Columbia

Abstract: The scyphomedusa Aurelia aurita in Saanich Inlet, a north-south oriented fjord in British Columbia, uses a sun compass to migrate in a southeasterly direction during the day. When the sky is overcast and at night, A. aurita orients randomly and is dispersed passively by gentle tidal currents. The net result is daily reaggregation of medusae into enormous swarms along the southeastern shore of the fjord. Observations of spawning A. aurita in these swarms suggest that sun-compass migration and aggregative behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
2
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(69 citation statements)
references
References 38 publications
(33 reference statements)
2
64
2
1
Order By: Relevance
“…The unit stock for the New South Wales jellyfish fishery should, therefore, be considered to be a population within an estuary. This conclusion is probably also relevant to species in other parts of the world, particularly where populations appear to be topographically confined, such as in fjords (Grondahl 1988, Hamner et al 1994) and estuarine lakes with restricted access to the open ocean (Hamner & Hauri 1981, Garcia 1990, Lucas et al 1997. The New South Wales jellyfish fishery is currently managed as a single stock, with 1 quota set for the entire fishery.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The unit stock for the New South Wales jellyfish fishery should, therefore, be considered to be a population within an estuary. This conclusion is probably also relevant to species in other parts of the world, particularly where populations appear to be topographically confined, such as in fjords (Grondahl 1988, Hamner et al 1994) and estuarine lakes with restricted access to the open ocean (Hamner & Hauri 1981, Garcia 1990, Lucas et al 1997. The New South Wales jellyfish fishery is currently managed as a single stock, with 1 quota set for the entire fishery.…”
Section: Resultsmentioning
confidence: 98%
“…Such patchiness was exhibited by Catostylus mosaicus and reflected by the large variation in abundance that occurred at the scale of sites within estuaries, as well as among replicate transects. Aggregation of medusae may be facilitated by oceanographic features (Larson 1992), but the distribution of large plankton, in particular, may not be explained by current movement alone (Hamner et al 1994). Organisms are likely, therefore, to use a combination of behaviour and oceanographic features to control their distribution.…”
Section: Linkages Among Estuariesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study horizontal swimming was assumed to be generally less important in comparison to the flow fields. Hamner et al (1994) reported average horizontal swim speed during day times of 2.33 ± 0.30 m min -1 with very slow or no swimming during the night while the western Baltic Sea shows average current speeds above 3 m min -1 . Nonetheless, to avoid too disperse scatter the annual simulation runs were stopped in June and new drifters restarted from the release areas in the following year.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this view, the following observations confirm rest -possibly sleep -in medusae of Aurelia aurita, in the class, Scyphozoa, which have only two tiny, non-lensed ocelli, of different composition (see [17]), on each of their eight rhopalia. ''In the dark, the medusae were quiescent, with bell contraction rates reduced or absent……on still nights medusae covered the surface……animals were almost motionless……'' [28].…”
mentioning
confidence: 99%